Obbligo vaccinale e rapporto di lavoro (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The article analyzes the legislative measures enacted during the pandemic situation from the standpoint of the labour law. In particular, the study focused on the compulsory vaccination in the perspective of labour law. The article focuses on the resolved and unresolved issues of the subject in the light of pandemic law.
Keywords: Pandemic; Labour law; Employment contracts; Vaccination